Peran Air Tawar Dalam Menunjang Kelancaran Pengoperasian Purifier Bahan Bakar dan Minyak Pelumas di Atas Kapal MV. Sinar Sabang - Agus Saleh; Eka Darmana (JURNAL BARTEK, 2025)
The purifier on board is one of the auxiliary machines which has a very important role to produce clean fuel. The use of this clean fuel is to support the operation of the ship's main propulsion engine and diesel generator engines in producing perfect combustion. In the operation of this purifier, Purifier operation often gets less attention that fresh water is very important to support the functioning of the purifier when working to purify fuel from liquid impurities and other solid impurities, because the function of fresh water in its operation includes operating water, sealing water and de sludge water. The data collection method used in this research was direct observation on the MV Sinar Sumba ship, literature study by reviewing manual books and discussions with engineers on board. From the data during the observation, literature study and interviews then analyzed and formulated and put forward using a qualitative descriptive method. The results of this discussion explain that in the purifier there are several parts that are very closely related to the smoothness and results of fuel refining, one of which is fresh water, because if fresh water is not available according to the required standards pressure and capacity, the purifier is not will be able to function properly. For example, if there is not enough fresh water that functions as a sealing water, then the oil will come out and be wasted through the water channels into the dirty oil tank.